Konsep Desain Lansekap Areal Selamat Datang Fakultas Pertanian Universitas Udayana Kampus Bukit Jimbaran, Bali - HAMONANGAN, AULIA AKBAR ISMAIL; SARWADANA, SANG MADE; YUSIANA, LURY SEVITA (Jurnal Arsitektur Lansekap; Vol.1, No.1, April 2015DO - 10.24843/JAL.2015.v01.i01.p02, 2015)
ABSTRACT Landscape Design Concept of Faculty of Agriculture Welcome Area in Udayana University Jimbaran Campus, Bali Campus is an area which multi-segment interactions will be taking place, the landscape situation has to manage to create a fine condition and gain good quality of education inside. As a front yard area which will be passed through by everybody who wants to come inside the campus welcome area has to raise any good impression and able to support the students requirement area to do their campus activities. This research has purpose to create a concept of landscape design of welcome area which has values of aesthetic, functional,  and creating landscape identity of faculty of agriculture the University of Udayana.  This researh has four steps: site measuring, inventaritation, analysis and syntesis, and creating the concepts. The concept of design is formal with Bali traditional arrangement. The concept will aplicate some principals of design such as balance, proportion, repetation, scale, and use shapes streinght and simetry. The concept of space create from Balinese local traditional wisdom the Tri Hita Karana (three source of happiness). The final products are concept plan and some drawings of 3D ilustration. Design concept with traditional Bali arragement wish to be aplicated by all of institution in the University of Udayana to create a unity of landscape which based on Bali local wishdom. Keywords: bali, campus, landscape design, udayana, welcome area